Monograph of the Spathidiida (Ciliophora, Haptoria) Vol I: Protospathidiidae, Arcuospathidiidae, Apertospathulidae - Foissner, Wilhelm; Xu, Kuidong; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
The spathidiids belong to the ciliate subclass Haptoria (Protozoa, Ciliophora), that is, they are predators using toxicysts to overwhelm the prey. Over 200 nominal spathidiid species have been described, sometimes based on seemingly minute differences. Thus, many protozoologists considered them as indeterminable and claimed for a detailed revision. The present monograph carefully revises the taxonomy, nomenclature, and ecology of all nominal species and shows that spathidiid diversity has been greatly underestimated. Based on the reinvestigation of described species with modern methods (silver impregnation, scanning electron microscopy) and the first description of over 50 new species, the family Spathidiidae is split into four families and 20 genera. Each species is described and figured in detail, making it unnecessary to go back to the original literature often difficult to obtain. Two identification keys are provided, viz., one for taxonomists and another, simple key for users not specifically trained in ciliate taxonomy.
General Section -- Systematic Section -- Family Protospathidiidae nov. gam. -- Family Arcuospathidiidae nov. fam. -- Family Apertospathulidea FOISSNER, XU & KREUTZ, 2005.
Keywords: LIFE SCIENCES; BIODIVERSITY; ZOOLOGY; LIFE SCIENCES; ZOOLOGY; ANIMAL SYSTEMATICS/TAXONOMY/BIOGEOGRAPHY.; BIODIVERSITY